IMPLIKASI KERJASAMA YANG SIMULTAN ANTARA KELUARGA, SEKOLAH, DAN MASYARAKAT DALAM PENDIDIKAN ISLAM DENGAN PENDEKATAN SOSIOLOGIS - AHMAD ABDUL QISO; KMS BADARUDDIN (Raudhah - Proud To Be Professional, 2022)
The educational process will not run effectively without simultaneous cooperation between the three main components of education, namely the family, school and community. However, in the practice of Islamic education, it turns out that there are still many obstacles. This is because there are still many people/parents who do not understand the fundamental meaning of their role in education. Therefore, this article was written with the aim of (1) analyzing the concept of simultaneous cooperation between families, schools and communities; and (2) Identify the implications of simultaneous collaboration between families, schools and communities in Islamic education. To carry out this research, library research was used with a philosophical approach, data collection techniques using documentation and data analysis techniques using content analysis. The results of this study indicate that: (1) In cultivating simultaneous collaboration between families, schools and communities, one of the theories that can be used is Epstein's Overlapping Spheres of Influence theory. This theory views that each component, namely the family, school, and community has a shared responsibility in creating an effective educational process; and (2) The implications of this collaboration for Islamic education, namely: (a) Fostering the birth of social capital in Islamic education; (b) Growing superior student personality both intellectually and emotionally; and (d) Improving the quality of Islamic education.